Impressionist Art in Private Clubs: The Case Study of the Union League Club (1886-1902) - Claire Hendren (Transatlantica)
Americans became acquainted with French Impressionism in the last decades of the nineteenth century. Surprisingly, private clubs were some of the first to endorse the movement, hosting impressionist exhibitions early on in the movement’s arrival to the United States. Using New York’s Union League Club as a case study, this article highlights the motivations and impact, both aesthetic and political, of the club’s approval of Impressionism. Not only did impressionist art become a way for club members to assert their advanced taste in art, but the Union League Club’s early praise of Impressionism, this essay argues, was key to the country’s reception of the movement.